Pemakaian Gaya Bahasa Pelatih Olahraga pada Pembelajaran Olah Raga Sepak Bola - Lukman Alfaris; Jamaludin Yusuf; Gilang Nuari Panggraita; Wilda Hamisa; Liyant Maihendra Anggara (Departement of Mathematics Education, 2023)
Different human backgrounds must have different language styles, as well as in conveying communication or information. From a different person's background, different language variations or varieties of languages ​​arise. The style of language varies depending on the background of the speakers, both educational and professional backgrounds and the interests of the speakers. For example, when a football coach explains something to the players, where the teams face each other, and each team has eleven players. Outdoor and indoor communication must be different, not to be equated because it affects the volume, so speakers must pay attention to volume. For example, a football coach in an open room must use a loud voice, but not only that, persuasive or motivational language will increase the enthusiasm of the football players. The data collection technique in this study analyzed data and recorded data containing language styles in the speech acts of football coaches. The method used is descriptive qualitative.